Etiology of Hypopituitarism in Adult Patients: The Experience of a Single Center Database in the Serbian Population - M. Doknić; S. Pekić; D. Miljić; I. Soldatović; V. Popović; M. Stojanović; M. Petakov (International Journal of Endocrinology)
There are only a few published studies related to the population-based etiology of hypopituitarism. New risks for developing hypopituitarism have been recognized in the last 10 years. Aim. To present data regarding the etiology of hypopituitarism collected in a tertiary center over the last decade. This is a cross-sectional database study. Patients and Methods. We included 512 patients (pts) with hypopituitarism, with a mean age of 45.9 ± 1.7 yrs (range: 18–82; male: 57.9%). Results. Nonfunctional pituitary adenomas were presented in 205 pts (40.5%), congenital causes in 74 pts (14.6%), while acromegaly and prolactinomas were presented in 37 (7.2%) and 36 (7.0%) patients, respectively. Craniopharyngiomas were detected in 30 pts (5.9%), and head trauma due to trauma brain injury-TBI and subarachnoid hemorrhage-SAH in 27 pts (5.4%). Survivors of hemorrhagic fever with renal syndrome (HFRS) and those with previous cranial irradiation were presented in the same frequency (18 pts, 3.5% each). Conclusion. The most common causes of hypopituitarism in our database are pituitary adenomas. Increased awareness of the other causes of pituitary dysfunction, such as congenital, head trauma, extrapituitary cranial irradiation, and infections, is the reason for a higher frequency of these etiologies of hypopituitarism in the presented database.